2020
DOI: 10.4102/td.v16i1.751
|View full text |Cite
|
Sign up to set email alerts
|

The big five personality traits influencing habitual Facebook usage, life satisfaction and psychological well-being of Generation Y students

Abstract: This research determined five big personality traits that influenced South African Generation Y students’ habitual use of Facebook, life satisfaction and psychological well-being. The research embraced a quantitative approach, and a structured questionnaire was used to obtain information from Generation Y students. The data were analysed using Smart PLS software version 3.2.7 for partial least square structural equation modelling (PLS-SEM). Neuroticism, extraversion, openness and agreeableness had positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…It is imperative to compare and contrast the results of the current study with the results of Maziriri's (2020) study. According to Maziriri's (2020)…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is imperative to compare and contrast the results of the current study with the results of Maziriri's (2020) study. According to Maziriri's (2020)…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…It is imperative to compare and contrast the results of the current study with the results of Maziriri's (2020) study. According to Maziriri's (2020) research, personal traits such neuroticism ( β = 0.451; t = 3.137), extraversion ( β = 0.129; t = 1.973), openness ( β = 0.331; t = 5.984) and agreeableness ( β = 0.156; t = 1.994) showed positive and significant effects on habitual Facebook usage. Additionally, Maziriri's (2020) research revealed that there was an insignificant relationship between conscientiousness and HFU ( β = 0.056; t = 0.803).…”
Section: Methodological Aspectsmentioning
confidence: 99%
See 3 more Smart Citations